Ethnobotany of indigenous (Traditional) vegetables in Adi tribe of East Siang region of Arunachal Pradesh, India - Md. Ramjan Chandra Deo; Chandra Deo; L. Wangchu; P. Sarma; Amit Kumar Singh; Shivani Dobhal (Environment Conservation Journal, 2021)
Arunachal Pradesh is known as land of rising Sun which is the biggest in terms of area-wise amongst the state of north east India.The region has 26 major tribe; each tribe has its own enormous indigenous knowledge on the uses of wild plants. Among the tribe, Adi community is one of the major tribe inhabited in the region which has its own habitual way of using horticultural (vegetables) resources for sustaining livelihood. Most of the plants are also ethnically important without wich diverse rituals and festivals (Solung) of adi community remain unfinished. The current servey was under taken interviewed through planned questionaire. In our investigation among 25 wild species, 5 species belong to the Solanaceae family which was found to be most widely used family followed by Apiaceae, Rutaceae, Urticaceae and Araceae. Investigation on the basis of plant parts used reveals that the edible parts of the plants such as 6 species found to be widely used though leaves followed by 3 species fruits and 3 species whole plants besides these other plant parts like young tender leaves, tender stalks, petioles, rhizome also has been observed. This study is aim to initiated the basic information of these valuable herbs vegetable species for popularizing in future. These can compete with the best vegetables if appropriate study is initiated for production and ethanomedicine improvement.